Хирургическая тактика при острой опухолевой толстокишечной непроходимости = Surgical tactics in acute colonic obstruction of tumor genesis - Drobkov, A. L.; Shapovalov, V. Yr.; Gerasiminko, O. S.; Davidov, D. M. (Journal of Education, Health and Sport, 2015)
Drobkov A. L., Shapovalov V. Yr., Gerasiminko O. S., Davidov D. M. Хирургическая тактика при острой опухолевой толстокишечной непроходимости = Surgical tactics in acute colonic obstruction of tumor genesis. Journal of Education, Health and Sport. 2015;5(11):78-84. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33366 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A78-84 https://pbn.nauka.gov.pl/works/666654 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.09.2015. Revised 05.10.2015. Accepted: 30.10.2015. ХИРУРГИЧЕСКАЯ ТАКТИКА ПРИ ОСТРОЙ ОПУХОЛЕВОЙ ТОЛСТОКИШЕЧНОЙ НЕПРОХОДИМОСТИ Surgical tactics in acute colonic obstruction of tumor genesis А. Л. Дробков, В. Ю. Шаповалов, О. С. Герасименко, Д. М. Давыдов A. L. Drobkov, V. Yr. Shapovalov, O. S. Gerasiminko, D. M. Davidov Одесский национальный медицинский университет Кафедра общей хирургии и военной медицины Odessa National Medical University The department of general surgery and military medicine Summary The article deals with the problem of surgical treatment of complicated forms of colon cancer, discussed the results of staged treatment of tumors of the colon against the background of acute intestinal obstruction. A retrospective analysis of 87 patients with tumors of the right and left half of the colon. The highest percentage of poor outcomes obtained from patients with colon cancer in stage IV. Postoperative mortality was 7-9%, 30-35% of complications. Key words: Surgery, Surgical treatment, colonic obstruction, tumor. Резюме В статье рассмотрены проблема тактики хирургического лечения осложненных форм рака ободочной кишки, обсуждены результаты этапного лечения опухолей толстой кишки на фоне острой кишечной непроходимости. Проведен ретроспективный анализ 87 больных с опухолями правой и левой половины толстой кишки. Наибольший процент неблагоприятных исходов получен у больных с раком ободочной кишки в IV стадии. Послеоперационная летальность составила 7-9%, осложнения 30-35%. Ключевые слова: хирургия, хирургическое лечение, кишечная непроходимость, опухоль. Резюме Хірургічна тактика при гострій пухлинної товстокишковій непрохідності. У статті розглянуто проблема тактики хірургічного лікування ускладнених форм раку ободової кишки, обговорені результати етапного лікування пухлин товстої кишки на тлі гострої кишкової непрохідності. Проведено ретроспективний аналіз 87 хворих з пухлинами правої і лівої половини товстої кишки. Найбільший відсоток несприятливих результатів отриманий у хворих з раком ободової кишки в IV стадії. Післяопераційна летальність склала 7-9%, ускладнення 30-35%. Ключові слова: хірургія, хірургічне лікування, кишкова непрохідність, пухлина.